Urinary Tract Stones Risk Factors in Patients with Benign Prostatic Hyperplasia in West Java, Indonesia - Iman Surendroputro Tjahjodjati; Bambang Sasongko Noegroho; Aaron Tigor Sihombing (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Urinary tract stones are common in patients with benign prostatic hyperplasia (BPH); therefore, an imaging test is needed for patients who have risk factors for the formation of urinary tract stones. The purpose of this study was to explore the factors associated with the presence of urinary tract stones in patients with BPH as information to conduct imaging tests.Methods: A cross-sectional quantitative analytic study was conducted on medical records of patients with BPH, both with and without urinary tract stones, or patients with urinary tract stones registered at the Department of Urology, Dr. Hasan Sadikin General Hospital, Indonesia, from 2015 to 2018. Data on age, body mass index, hypertension, use of antihypertensive drugs, diabetes mellitus, and hyperuricemia were collected and analyzed using the Mann-Whitney, Chi-square, Fisher exact test, and multivariate logistic regression statistical test to compare variables between BPH with and without urinary tract stones.Results: In total, 235 BPH patients were registered, of whom 74 (31.5%) had urinary tract stones. The median age was 64 years old. There was a relationship between age (p=0.030), diabetes mellitus (p=0.043), and the occurrence of urinary tract stones in patients with BPH. The most dominant risk factor was diabetes mellitus (OR=3.000, 95%CI 1.03-8.69).Conclusions: Age and diabetes mellitus are the risk factors for urinary tract stones in patients with BPH. BPH patients with diabetes mellitus are at a 3-fold risk for urinary tract stones. Diabetes mellitus in BPH patients is an indication to conduct imaging tests.